2019
DOI: 10.12688/wellcomeopenres.15073.1
|View full text |Cite
|
Sign up to set email alerts
|

India Research Management Initiative (IRMI) – an initiative for building research capacity in India

Abstract: Research and innovation are growing in India with significant investments being made towards institutions, researchers and research infrastructure. Although still under 1% of GDP, funding for science and technology in India has increased each year for over two decades. There is also increasing realization that public funding for research should be supplemented with that from industry and philanthropy. Like their counterparts worldwide, Indian researchers require access to professional research management suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In India, the India Research Management Initiative, a research capacity-building programme, was launched in February 2018 to help create awareness for research management, engage in dialogue with Indian institutions and build a baseline of information to base future policy development and funding opportunities on [46]. The challenges to research capacity-building include lack of leadership support for research management, lack of administrative support and inadequate career development for researchers [46]. The African Mental Health Research Initiative is a mental health research capacity-building initiative established in 2015 [47].…”
Section: Mental Health Clinical and Research Capacity-buildingmentioning
confidence: 99%
“…In India, the India Research Management Initiative, a research capacity-building programme, was launched in February 2018 to help create awareness for research management, engage in dialogue with Indian institutions and build a baseline of information to base future policy development and funding opportunities on [46]. The challenges to research capacity-building include lack of leadership support for research management, lack of administrative support and inadequate career development for researchers [46]. The African Mental Health Research Initiative is a mental health research capacity-building initiative established in 2015 [47].…”
Section: Mental Health Clinical and Research Capacity-buildingmentioning
confidence: 99%
“…Although research is increasingly recognized as one of the dynamic forces behind global health and development, the research output from low- and middle-income countries such as India compares poorly with high-income countries [ 6 ]. Quality research output from India is grossly lacking, and there is relatively little research output in several diseases/ conditions that cause a significant disease burden in India [ 7 ]. A study conducted by Dandona et al revealed that many leading causes of disease burden across communicable, non-communicable diseases, injuries, and other health priorities continued to be underrepresented in public health research output [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research and innovation are growing in India, with significant investments being made towards institutions, researchers, and research infrastructure [ 7 ]. Multiple fellowships have been offered at a national and global scale for capacity building in public health research; however, the difficulties faced during public health research grant management are poorly researched.…”
Section: Introductionmentioning
confidence: 99%